Self-Reliant Rainwater Harvesting System Guidelines (RWHS) for Non-Potable Water Usages - Mohd Zamri, Nur Sarah Afiqah; Rahmat, Siti Nazahiyah (Recent Trends in Civil Engineering and Built Environment, 2021)
Malaysia is a rapidly developing country that receives a high amount of rainfall each year. However, the increase in population in Malaysia has led to the issue of a water crisis. Concerning this issue, the Ministry of Housing and Local Government (MHLG) has proposed installing a Rainwater Harvesting System (RWHS) as one of the solutions. Nevertheless, the current constraints on the installation of a rainwater storage system in the market are costly, and skilled workers are needed. Therefore, a self-reliant RWH manual for non-potable water usage was designed. In the current study, Bangunan Tapak Semaian UTHM was chosen as the study area. The harvested water is used to water about 2000 plants. This manual is very useful to assist and disseminate RWHS knowledge to the public. It consists of design steps, including the water storage tank, gutter, first flush diverter, connector pipes, and installation of RWHS. In conclusion, the proposed manual gives the simplest guide for designing, building, and maintaining the system. It is hoped that this may increase the public awareness on the advantages and benefits of installing RWHS and can be fostered in the future.